THE EFFECT OF LABOR AND INVESTMENT ON THE GRDP OF NORTH MALUKU PROVINCE - Marsida Marsida; Didit Welly Udjianto (Yayasan Education and Social Center, 2023)
Unemployment is one of the development issues confronting Indonesia, including North Maluku Province. To determine how much North Maluku Province's economic growth can absorb labor to reduce unemployment, it is necessary to conduct an analysis based on labor growth. The reality is that the high economic growth rate only sometimes guarantees significant employment absorption. A high economic growth rate only sometimes ensures effective employment absorption. This study aims to determine whether investment and labor have a partial or simultaneous effect on the Gross Regional Domestic Product of the Regency/City in North Maluku Province over the period of 2010-2018. The results of partial hypothesis testing show that the labor variable (X1) affects North Maluku's GRDP. It is supported by the obtained t value of 2.19 > t table of 1.99 and a significant deal of 0.033 <0.05. Ha is accepted, and Ho is rejected, meaning that variable X1 affects variable Y (GDP) of North Maluku. Besides that, the results of partial hypothesis testing show that the labor variable (X2) affects North Maluku's GRDP. This is supported by the obtained t value of 4.55 > t table 2.17 and the sign value. 0.000, then Ho is rejected, and Ha is accepted, meaning that the variable X2 affects Y (GDP) of North Maluku. And finally, the findings of the simultaneous testing of hypotheses show that both X1 and X2 impact Y. This conclusion is supported by an adjusted R square value of 0.6965, which translates to 69.65% of the total